Geografinės informacijos skaitymas edukacinės komunikacijos požiūriu - Kairaitis, Zigmas (Information & Media, 2007)
Straipsnio tikslas – pasitelkus komunikacijos ir informacijos mokslų idėjas, atskleisti pagrindinių ugdymo proceso dalyvių – mokytojo, mokinio, dalyko (geografijos) – edukacinės sąveikos turinį ir išryškinti geografinės informacijos interpretavimo edukacinės komunikacijos perspektyvą. Komunikacijos ir informacijos mokslų vystimasis pasiekė tokį lygmenį, kai kažkada buvę kaip atskiri mokslai arba jų samplaika, nūdien tapo tarpdisciplininiu mokslu. Atskirų disciplinų edukacijoje informacija ir komunikacija tapo sudėtine ugdymo turinio ir proceso dalimi. Geografija kaip integruotas mokslas ir mokomasis dalykas yra palankus įvairiems komunikacijos modeliams, būdams taikyti. Geografinėje informacijoje glūdi pažintinės vertybės, kurių neįmanoma tiesiogiai išmokti – jas reikia išgauti, susiformuoti. Vienas iš tokių būdų, padedančių informacijai suteikti vertybinę esmę, yra klausimų kėlimas. Komunikuojant klausimais sukuriama daugiakryptė (sinerginė) edukacinė erdvė, kai pagrindiniai ugdymo proceso dalyviai (mokytojas, mokinys, dalykas) yra lygiaverčiai pažinimo vertybių kūrimo atžvilgiu. Reading of geographical information in terms of educational communication Zigmas Kairaitis Summary The article deals with geographical information reading referring to a communicative relation with a text. With the help of ideas of communication and information sciences, the content of an educational interaction of the main participants in the training process, i.e. a teacher, student, subject (geography), is revealed as well as educational communication prospects of geographical information interpretation are highlighted. Recently, with the formation of a favourable methodological discourse, an insight to knowledge, a training process and culture phenomena in another aspect, i.e. a communicative aspect, becomes possible. These issues are related to the development of an information and knowledge society. Communication covers much more than just conveyance of information and knowledge. In education, communication manifests itself as an instrument of educational interaction and serves as an intermediate between the matters expressed through the message and matters accepted through the message. As an integrated science and subject, geography is favourable for application of different communication models and methods. Geographical information contains cognitive values that cannot be learnt directly – they shall be drawn out, developed. One of such ways that help to provide information with worthwhile essence is question raising and answering the questions raised. Communication of questions leads to the formation of multidirectional (synergetic) educational space when all participants of the training process (a teacher, student, subject) are equivalent in respect of development of cognitive values. Quintessence of the article: an included educational communication model.